2018
DOI: 10.1561/2000000103
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on the Low-Dimensional-Model-based Electromagnetic Imaging

Abstract: The low-dimensional-model-based electromagnetic imaging is an emerging member of the big family of computational imaging, by which the low-dimensional models of underlying signals are incorporated into both data acquisition systems and reconstruction algorithms for electromagnetic imaging, in order to improve the imaging performance and break the bottleneck of existing electromagnetic imaging methodologies. Over the past decade, we have witnessed profound impacts of the low-dimensional models on electromagneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 143 publications
0
17
0
2
Order By: Relevance
“…In this way, a sequence of quasi-random radiation patterns can be generated by managing the applied voltages of information metasurface, which could provide adequate measurement modes for the high-quality image. For reducing the complexity of controlling the bias voltages of the information metasurface, Li et al proposed that the meta-atoms be manipulated in the column-row-wise manner [84]. Specifically, the information metasurface with N x × N y meta-atoms is controlled by using N x + N y coding sequences.…”
Section: Programmable Imagermentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, a sequence of quasi-random radiation patterns can be generated by managing the applied voltages of information metasurface, which could provide adequate measurement modes for the high-quality image. For reducing the complexity of controlling the bias voltages of the information metasurface, Li et al proposed that the meta-atoms be manipulated in the column-row-wise manner [84]. Specifically, the information metasurface with N x × N y meta-atoms is controlled by using N x + N y coding sequences.…”
Section: Programmable Imagermentioning
confidence: 99%
“…Specifically, the information metasurface with N x × N y meta-atoms is controlled by using N x + N y coding sequences. More interestingly, they theoretically and experimentally demonstrated that the very simple column-row-wise coding metasurface has a theoretical guarantee to ensure that the required measurement number is comparable to that for the conventional pixel-wise encoded masks, while simultaneously maintaining nearly the same imaging quality [84].…”
Section: Programmable Imagermentioning
confidence: 99%
“…For the conventional imaging technologies, arrays of detectors are required to sense the characters of EM field at the imaging plane. A new cutting‐edge imaging method, single‐sensor imaging, has been proposed and applied in many applications . Only one detecting source is need instead of the source array in the single‐sensor system.…”
Section: Programmable Metamaterialsmentioning
confidence: 99%
“…Programmable metamaterials enable the wave‐based information coding and processing on the physical level of metamaterials in real time. The holograms and image system based on the programmable metamaterials have been proposed and reported . These systems rely on the active and dynamic manipulation of EM waves which push the programmable image systems to have low cost and more flexibility in real applications.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…Metasurfaces, the 2D version of MTMs, are drawing more and more attention and have become the new hot spot in the research of MTMs . Governed by the generalized Snell's laws of reflection and refraction, the abrupt phase changes on the interface as well as the surface impedances are modulated so as to realize desired functionalities, such as the manipulating the polarization of EM waves, holographic imaging and transforming wavefronts . It has also been used in the conversion of spatially propagating waves to surfaces waves .…”
Section: Metasurfaces and Other State‐of‐the‐art Microwave Mtmsmentioning
confidence: 99%